2014
DOI: 10.4161/21623945.2014.981434
|View full text |Cite
|
Sign up to set email alerts
|

The proliferation and differentiation of primary pig preadipocytes is suppressed when cultures are incubated at 37°Celsius compared to euthermic conditions in pigs

Abstract: Given similarities in metabolic parameters and cardiovascular physiology, the pig is well positioned as a biomedical model for metabolic disease and obesity in humans. Better understanding molecular mechanisms governing porcine adipocyte hyperplasia may provide insight into the regulation of adipose tissue development that is useful both when considering the pig as a commodity and when extrapolating porcine data to human disease. Primary cultures of pig stromal-vascular cells have served as a useful tool for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…The culture of swine enteroids, although challenging, has been previously reported in studies showing the presence of all cells of the intestine and their response to bacterial lipopolysaccharide stimulation [ 27 , 53 , 54 ]. The swine enteroids grown in our laboratory showed similar characteristics to those reported in previous studies, although we have defined that culturing at 39°C (the body temperature of pigs) favors the expression of differentiation markers, as has been previously suggested for adipocytes [ 55 ]. There is limited information in the literature about the regulation of mucin in swine.…”
Section: Resultssupporting
confidence: 69%
“…The culture of swine enteroids, although challenging, has been previously reported in studies showing the presence of all cells of the intestine and their response to bacterial lipopolysaccharide stimulation [ 27 , 53 , 54 ]. The swine enteroids grown in our laboratory showed similar characteristics to those reported in previous studies, although we have defined that culturing at 39°C (the body temperature of pigs) favors the expression of differentiation markers, as has been previously suggested for adipocytes [ 55 ]. There is limited information in the literature about the regulation of mucin in swine.…”
Section: Resultssupporting
confidence: 69%
“…In this regard, Shu et al described the role of phloretin, which promotes the differentiation of 3T3-L1 adipocytes, and demonstrated that phloretin enhances the lipid accumulation in a time-dependent manner in porcine primary adipocytes [ 76 ]. In another study, primary cultures of pig SVF cells were differentiated to study the effect of temperature on proliferation and differentiation [ 77 ]. Furthermore, retinol binding protein 4 (RBP-4) was observed to significantly suppress differentiation in porcine preadipocytes by decreasing the activation of insulin signaling pathways [ 78 ].…”
Section: Animal Cell Modelsmentioning
confidence: 99%
“…Addition of a PPARγ agonist for 48 h improved differentiation, increasing medium-sized lipid droplet formation (Fig. 2b1) and suggesting that similar to feline [7], porcine [34], and human [31] preadipocytes, ovine preadipocytes have lower sensitivity to insulin than murine cell lines and PPARγ agonist may be a more stringent requirement for adipogenic differentiation in these species.…”
Section: Resultsmentioning
confidence: 99%
“…They also require higher insulin concentration during differentiation to enhance lipid accumulation and similar to human primary preadipocytes [ 21 , 22 ], PPARγ agonist supplementation is also required for ovine adipogenic differentiation. This work highlights species-specific differences requirements for adipogenic differentiation [ 7 , 14 , 31 , 34 ] and the need to develop standardized methods to investigate comparative adipocyte biology.…”
Section: Resultsmentioning
confidence: 99%